Management of Third World Crises in Adverse Partnership : Theory and Practice - Bokhari, Imtiaz H. (Rawalpindi, Pakistan Army Education Publishing House, 2002)
Imtiaz Bokhari details the world response to three regional conflicts--the 1973 Arab-Israeli war, the 1971 Indo-Pak crisis, and the Iran-Iraq war--and analyzes the dynamics of the comcomitant international crisis management. There exists a greater need for crisis management, the author argues, in a international system in which the disintegration of the old superpower competition and restraints has changed the rules of the game to the apparent advantage of the stronger regional powers.
Include Bibliography and Index
Keywords: International relations -- India-Pakistan Conflict (1971) -- Crisis management -- Iran-Iraq War (1980-1988) -- Israel-Arab War (1973) -- Peace